Human-induced biospheric carbon sink: Impact from the Taklamakan Afforestation Project - Salma Noor; Xun Jiang; Xinyue Wang; Jiani Yang; Sally Newman; King-Fai Li; Liming Li; Le Yu; Xiyu Li; Yuk L. Yung (Proceedings of the National Academy of Sciences, 2026)
The Taklamakan Desert, one of the world’s largest and driest deserts, has traditionally been considered a biological void. Here, we demonstrate that large-scale ecological restoration is transforming this hyperarid environment into a carbon sink. By analyzing satellite and ground-based data, we find strong seasonal dynamics: During the wet season (Jul to Sep), precipitation increases to 16.3 mm/mo, enhancing vegetation coverage and photosynthetic activity and drawing down atmospheric CO 2 by approximately three parts per million (ppm) relative to the dry-season levels. Long-term trends reveal significant increases in vegetation cover (6.8 × 10 −4 /y) and photosynthetic activity (6.1 × 10 −3 W/m 2 /sr/µm/y), accompanied by a strengthening net CO 2 uptake (NEE trend: −5.2 × 10 −12 kg/m 2 /s/y). These changes are spatially concentrated along the desert margins and their timing aligns with implementation of China’s Three-North Shelterbelt Program. Our results provide the direct evidence that human-led intervention can effectively enhance carbon sequestration in even the most extreme arid landscapes, demonstrating the potential to transform a desert into a carbon sink and halt desertification. This underscores the critical role of dryland restoration in global carbon management strategies and highlights the Taklamakan Desert as a model for climate change mitigation through nature-based solutions and ecological engineering.